Chemo-Enzymatic Epoxidation of Unsaturated Fatty Acids - Orellana Coca Åkerman, Cecilia (Biotechnology, Lund University, 2006)
Epoxy fatty acids are useful molecules and find a number of applications e.g. as PVC plasticisers and stabilisers, additives in polyurethane production, reactive diluents in paints, corrosion protection agents, etc. Chemo-enzymatic epoxidation of unsaturated fatty acids has been studied; the peracid formation was catalysed by immobilised Candida antarctica lipase B (Novozym 435), and hydrogen peroxide was used as oxygen donor. A method based on HPLC for the analysis and quantification of unsaturated fatty acids and their epoxides was developed. The process of chemo-enzymatic epoxidation was optimised with an aim to minimise solvent use and maximise productivity. Epoxystearic acid and epoxystearic acid methyl ester were synthesised in very good yields in solvent free conditions, and is suggested to be a good alternative to the traditional epoxidation methods for epoxidation of fatty acids and oils. Subsequently, the effect of the reaction parameters on the epoxidation of linoleic acid was investigated. Hydrogen peroxide was found to have a significant effect on the reaction rate and degree of epoxidation. The same enzyme was then used to synthesise alkyl esters of epoxystearic acid, the esterification and perhydrolysis reactions being catalysed by the lipase in one pot. Butyl epoxystearate was synthesised with high yields. The parameters affecting lipase activity and operational lifetime during the chemo-enzymatic epoxidation were investigated. The high concentration of hydrogen peroxide used for the reaction inactivates the enzyme at high temperature, hence limiting recycling of the biocatalyst. Results suggest that temperature control and careful dosage of hydrogen peroxide are among the most important parameters for industrial chemo-enzymatic epoxidation.